Human and ecological risk assessment : theory and practice - Paustenbach, Dennis J., ....- (New York : Wiley, 2002)
Contents:--------a. Human health assessmentb. ecological risk assessmentc. Case studies involving contaminated waterd. Case study involving contaminated soilse. Characterizing exposure to air contaminantsf. Evaluating occupational hazardsg. Case study involving exposure to radionuclidesh. Evaluating risk to foodsi. Assessing risks associated with consumer productsj. Case studies in ecological risk assessmentk. Assessing risks to birdsl. Risk assessment and life-cycle analysesm. Risk communication and risk managementn. Evolving issuesAn authoritative guide to risk assessment, grounded in actual casestudies of sites or issues that address a wide range of human andecological hazards Human and Ecological Risk Assessment: Theory andPractice assembles the expertise of more than fifty authorities fromfifteen different fields, forming a comprehensive reference and textbookon risk assessment.
Keywords: Bodemverontreiniging; Luchtverontreiniging; Milieuaspecten; Risicobeheersing; Waterverontreiniging